101k views
2 votes
Raul simplified the expression, as shown below.

–[3h + 7h(2 – h)] = –[10h(2 – h)] = –[20h – h] = –19h

Describe the error(s) in Raul’s work.

2 Answers

5 votes

Answer:

he should have worked out 7h(2 - h) first before adding the 3h. (first step)

2nd step he multiplied the 2 by -10h but he also should have multiplied the -h by the -10h ( Distributive law)

Explanation:

Got it right on edge

User SHUBHAM SHEDGE
by
4.5k points
7 votes

Answer:

Raul's errors are in the application of the distributive property(he applied it wrongly), in not respecting the precedence of operations, and in the multiplication of two terms with the same base(we add the exponent).

Explanation:

Distributive property:

The distributive property of multiplication is:

a*(b + c) = a*b + a*c

Precedence of operations:

First multiplication, then addition.

Multiplication of terms with the same base:

The multiplication of h*h = h², which Raul missed.

The correct simplification is given by:


-[3h + 7h(2-h)] = -[3h + 14h - 7h^2] = -[17h - 7h^2]=7h^2 - 17h

User Greg Tarsa
by
5.2k points